A3.3 Micro-RNA-34a and micro-RNA-155 unbalance is associated to IL-6/IL-6R pathway in CD14 cells and skin compartment of systemic sclerosis patients. (13th February 2015) - Alivernini, S; Bosello, SL; Tolusso, B; Benvenuto, R; Mangoni, A; Bui, L; Canestri, S; Di Mario, C; Ferraccioli, G
Abstract : Background and objectives: MicroRNAs (miRs) are post-transcriptional regulators implicated in Systemic sclerosis (SSc). MiR-34a and miR-155 are related to endothelial senescence and inflammation. The aim of the study is to investigate the expression of miR-34a and miR-155 in peripheral blood (PB) CD14 cells and in clinically involved and uninvolved skin paired samples in SSc. Materials and methods: Twenty-seven patients with Raynaud phenomenon (RP) were enrolled, divided into 3 groups: long standing SSc (lsSSc) fulfilling the 1987 ACR criteria (n = 10), early SSc (eSSc) reaching 9 points using the Very Early Diagnosis of Systemic Sclerosis criteria (n = 9) and primary RP (n = 8) respectively. Matched healthy controls (HC) (n = 7) were enrolled. Immunostaining for CD68 was performed on paired skin tissues from SSc patients. miR-34a and miR-155 expression was evaluated by qPCR on CD14 cells isolated by CD14 specific microbeads from PB and on clinically involved and uninvolved skin paired samples. Using HumanTargetScan cross-referenced methodology, IL-6 receptor (IL6-R) was selected as target of miR-34a and miR-155 and experimentally confirmed by qPCR. IL-6 and IL-6R plasma levels were determined by ELISA. CD14 cells from PB of HC (n = 4) were cultured in RPMI, stimulated with IL-6 (30ng/ml) or LPS (100ng/ml) and collected after 48 h to assess miR-34a and miR-155 expression by qPCR. Results: MiR-155 is over-expressed either in eSSc (p = 0.0002) and lsSSc (p = 0.04) compared to HC. MiR-34a expression is increased only in lsSSc compared to HC (p = 0.01). Primary RP patients did not differ for miR-155 and miR-34a expression from HC (p = 0.71). CD68 cells are over-represented in clinically involved skin compared to uninvolved skin paired samples (p = 0.02). MiR-34a is over-expressed in clinically involved skin samples compared to uninvolved skin (p = 0.04). IL-6R expression is significantly lower in lsSSc and eSSc patients compared to primary RP (p = 0.03 and p = 0.03). IL-6 plasma levels were higher in lsSSc (p = 0.01) as well as in eSSc (p = 0.003) compared to HC whereas no significant difference was found in IL-6R plasma levels. MiR-34a expression directly correlates with the skin score value (R = 0.52, p = 0.03) in SSc patients and with IL-6 plasma levels (R = 0.42; p = 0.01). SSc patients with digital ulcers have higher miR-34a expression than SSc patients without ulcers (p = 0.01). Finally, miR-34a and miR-155 are induced in CD14 cells by IL-6 and LPS in vitro stimulation. Conclusions: MiR-34a and miR-155 expression is unbalanced in CD14 cells and paired skin samples of SSc patients linked to the IL-6/IL-6R pathway. MiRNA expression profile could help to differentiate patients with primary and SSc associated RP.